Herba extraction and optimization of essential oil from Chromolaena Odorata by using solventless extraction technique/ \c Nurul Suraya Rosli - Nurul Suraya Rosli (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
Traditionally, Chromolaena odorata is being used for its many medicinal properties especially for external uses as in wound, skin infections and inflammation. Extraction and characterization of essential oil from C. odorata can be done to discover the potential as medicinal herb. Essential oil carries the aroma of the plant which it be extracted. The current techniques used in extracting essential oil in the industry have their own drawbacks. In this study, solventless extraction technique has been used to extract essential oil from C. odorata. Optimization by using Response Surface Methodology through Central Composite Design (CCD) is done to study the optimum condition for this technique to produce high percentage yield of essential oil. The effect of temperature and time of extraction has been studied in this research. Through the study, the maximum yield of essential oil produced by this technique is at 100C and 8 hours, that is 0.1%. In order to compare the yield and quality of oil produced, hydro-distillation method was also conducted in this experiment. The essential oil extracted at this condition is then being analyzed by using Gas chromatography (GC) and Gas Chromatography Mass Spectrometry (GCMS) to identify the major compound.